Oyster reef enhancement utilizing gardened oysters in a subtropical estuary. Issue 5 (12th June 2019) - Anderson, Lacie; Sacks, Paul; Donnelly, Melinda; Barker, Virginia; Anderson, Samantha; Walters, Linda
Abstract : Crassostrea virginica, the eastern oyster, is a native foundational species that inhabits coastal and estuarine ecosystems along the western Atlantic seaboard. Introduction of C. virginica into estuarine areas with limited or no extant populations is gaining popularity as a pro‐active approach for improving estuarine water quality and creating natural wave breaks for shoreline stabilization. Adult oysters, grown by 113 community members under their private docks, were collected and deployed at three county‐owned sites along the Indian River Lagoon within Brevard County, Florida. In this shallow, warm‐water estuary, replicate treatments deployed at each site included bagged adult oysters collected from gardeners in fall 2014, bagged adult oysters from spring 2015 gardeners, bagged blank (clean) shell, and empty plots (control). Prior to deployment, morphometric data (shell length, weight) were collected on all gardened oysters. Morphometric data were then collected quarterly for all surviving and recruited oysters for 18 months. Our monitoring timeframe was sufficient for assessing survival of gardened oysters, but likely not sufficient to understand recruitment patterns. In areas with no recruitment and limited gardened oyster survival, regular enhancement with live oysters would be needed for long‐term success. In areas with natural recruitment, the blank shell treatment was most successful. Lessons learned from this study include: (1) need for better tracking of abiotic variables (e.g. salinity) where gardening occurred, (2) role of seasonality in initial post‐deployment survival, even in a warm‐water estuary, and (3) importance of pilot studies prior to large‐scale gardened oyster deployments.